Influence of Ice Accretion on Stratospheric Airship in the Non-Forming Ascending Process - Chenrui Fu; Ming Zhu; Yang Ding; Ping Tian; Mengyu Huang; Dongxu Liu; Da Zhao (Aerospace, 2022)
Ice accretion on stratospheric airships, which affects the net buoyancy and reduces the ascent speed, thereby leading to component failure and further necessitating flight termination, has received considerable attention. In this study, the formation of ice occurred when the airship hit supercooled water droplets during the non-forming ascending process. Theoretical descriptions of an ice accretion model, a thermal model, and a dynamic model for airships were established to estimate the flight performance with ice mass. Then, validation of the simulation and the cloud chamber test was carried out, which indicated that the temperature, liquid water content (LWC), and pressure considerably influenced the ice mass. A lower temperature had a positive effect on ice accretion. The mass of ice accretion increased with the increase in LWC. Ice did not form easily under low pressure due to evaporation and sublimation. Finally, the effects of the ambient LWC and initial helium mass were analyzed. It was shown that an LWC of 0.5 g/m3 resulted in severe degradation of the ascent performance. When the initial helium mass was not sufficient, the airship landed due to ice accumulation. However, redundant inflation increased the ice mass and lowered the cruising altitude.